METODE ISTINBÃT DALAM HUKUM ISLAM - Abidin Abidin (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2018)
This article deals with the use of nas to social fact, whether the social fact supprteed by nas of qur’an or of hadisclearly (the nas is zann al- wurud and zann al-dalalah) only, or is not supported by nas at all. When the social fact is supported by clear nas, then the law will be directly decided, and when the social fact is not supported by unclear nas, the will be conducted through the method of language and meaning istinbath. In the mean time, when the social fact is not supported by nas at all, then the istinbat will be conducted through the method of meaning istinbat.